IDENTIFICATION OF HERZBERG’S MOTIVATOR-HYGIENE FACTORS FOR SME’S WORKERS (Case Study of SME in West Java Province, Indonesia) - Ceicalia Tesavrita; Dedy Suryadi (Research Report - Engineering Science, 2012)
In general, an organization’s life cycle consists of 4 phases. Those phases are birth, growth, mature, and decline. In order to optimize an organization’s income, it should retain its growth and mature phases as long as possible. There have been quite a number of growing SME in West Java, however merely a fraction of them who is able to survive the growth phase. In order to survive, one of the main issues is to keep the workers motivated to achieve a good performance.There have been several theories explaining motivation, including the one offered by Herzberg. According to Herzberg, there are two groups of factors that contribute to motivation. They are motivator and hygiene factors. A person’s dissatisfaction may be eliminated by providing the hygiene factors, while a person’s satisfaction may be enhanced by providing the motivator factors. In this research, those factors are grouped further into 6 categories based on Kano model. Based on the categorization, it is clear which factors affect a person’s job satisfaction. In the context of SME, they would be able to prioritize the factors that they need to motivate the workers, keep the workers satisfied, and furthermore survive the growth phase.